Evaluation of modified atmosphere bag and sulphur dioxide concentrations applied on highbush blueberries fruit (Vaccinium corymbosum L.) cv. Emerald - Rodríguez, Mario (2015)
Aiming to evaluate techniques for modified atmosphere and application of sulphur anhydride upon parameters of quality of postharvest on blueberry fruit (Vaccinium corymbosum L.) cv. Emerald, an experiment of six treatments was conducted, given by the combination of two factors, modified atmosphere (with and without) and different concentrations of sulphur dioxide (generated by 0, 1 and 2 g of sodium metabisulphite) during 7, 14, 21 and 28 days at 0 °C. The dose of 2 g of modified atmosphere sodium metabisulphite showed no rotting, in contrast to the control treatment that showed a 4.86% after 28 days of storage. The results indicate that grey rot incidence decreased significantly (p ≤ 0.05) with sulfur dioxide in modified atmosphere bag, with an effect of interaction between both factors, however the gas that caused whitening damage on fruits, which corresponded to 11.66% with a dose of 2 g of sodium metabisulphite after 28 days of storage. The use of modified atmosphere bag reduced significantly (p ≤ 0.05) weight loss by dehydration (4% average) compared to treatments where this technology was not used. The concentration of soluble solids was not influenced by treatments, staying between 13% and 14%.